LEGAL RISKS IN NON-FUNGIBLE TOKEN (NFT) TRANSACTIONS - Rian Samya Weka Pratama; Tri Andari Dahlan (Universitas Negeri Semarang, 2026)
The advancement of blockchain technology has introduced Non-Fungible Tokens (NFTs) as digital assets representing ownership of creative works. However, the burgeoning NFT market precipitates significant legal risks, primarily arising from the dichotomy between the ownership of the digital token and the copyright of the underlying work. This research aims to examine the juridical risks inherent in NFT transactions, given the regulatory lacuna within the Indonesian legal system. Although Law No. 28 of 2014 concerning Copyright provides a normative framework, its application within the NFT ecosystem confronts challenges regarding legal certainty and platform accountability. The findings underscore the exigency of statutory harmonization and a more comprehensive legal protection mechanism, including defined liabilities for Electronic System Providers (ESPs), to mitigate risks and ensure equitable legal protection within Indonesia’s digital economy.